PELATIHAN ASESMEN IMPLEMENTASI KURIKULUM MERDEKA (IKM) BAGI GURU SEKOLAH DASAR KABUPATEN PROBOLINGGO - Anggraini, Ade Eka; Suciptaningsih, Oktaviani Adhi; Mardhatilah, Mardhatilah; Khotimah, Khusnul; Zativalen, Oriza; Sufian Kang, Enio Kang Mohd (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2024)
of Education Kec. The source and the service team concluded that the problems in the primary school include (1) the teacher's lack of understanding of the Merdeka Curriculum Implementation Assessment, because it is considered only for IPA subjects, (2) the unavailability of supporting book references in the classroom or library related to the assessment of Merdeka Curriculum Implementation, (3) the learning has not been touched by literacy and technology innovations, and (4) Learning in Education The Merdeka Curriculum is still alien to teachers. The solution to this problem is to carry out Focus GroupDiscussion (FGD) activities and training learning activities through the implementation of the Merdeka Curriculum Implementation assessment. Increasing the number of libraries is related to independent curriculum in learning, Independent curriculum learning training, Guidance of evaluation products of training results by teachers. External targets in this activity are to increase teachers' understanding of the concept of independent curriculum implementation assessment, document time schedule based student'activitys, (portfolio), reference book on Independent Curriculum Implementation Assessment for teachers (10 e-books from various sources), publication of activities in 1 mass media and 1 video of activity uploaded on youtube channel, 1 Draft evaluation result assessment of implementation of merdeka curriculum scientific articles in the form of an accredited journal (1 accredited journal article), 1 HKI.